Integration of Theo Jansen Mechanism Quadruped Robot with 5 Degree of Freedom Robotic Arm for Enhanced Motion Control - Chaudhary, Shubham; Karki, Anish Karki; Bhamare, Suhas; Shirsath, Subodh; Kawarw, Dr. Kiran (Journal of Advanced Mechanical Engineering Applications, 2024)
This paper presents an in-depth analysis of integrating a Theo Jansen mechanism quadruped robot with a 5-degree-of-freedom robotic arm, focusing on static structural and kinematic aspects. Using SolidWorks Simulation software and ABS material, components are analysed under various loads. Results show max stress, max displacement, and max strain values for each component. Gripper shows max stress 15050 kN/m², max displacement 2.755 mm, max strain 0.004 under 10 N load, Base shows max stress 310200 N/m², max displacement 0.02 mm, max strain 0.00009 under 30 N load. Shoulder, elbow, and wrist links also show distinct characteristics. Chassis under 20 N load shows max stress 2617 N/m², max displacement 0.000006 mm, max strain 0.000001. Kinematic analysis includes graph of end effector’s Linear Displacement, Linear Velocity, and Linear Acceleration with respect to time under a 100 RPM driving shaft speed.